The PB2 subunit of the influenza A virus RNA polymerase is imported into the mitochondrial matrix - Long, J; Fodor, E (American Society for Microbiology, 2016)
The PB2 subunit of the RNA polymerase complex of seasonal human influenza A viruses has been shown to localise to the mitochondria. Various roles including the regulation of apoptosis and innate immune responses to viral infection have been proposed for mitochondrial PB2. In particular, PB2 has been shown to inhibit interferon expression by associating with the mitochondrial antiviral signalling (MAVS) protein, which acts downstream of RIG-I and MDA-5 in the interferon induction pathway. However, in spite of a growing body of literature on the potential roles of mitochondrial PB2, the exact location of PB2 in mitochondria has not been determined. Here, we use Enhanced Ascorbate Peroxidase (APEX) tagged PB2 proteins and electron microscopy to study the localisation of PB2 in mitochondria. Wefind that PB2 is imported into mitochondria where it localises to the mitochondrial matrix. We also demonstrate that MAVS is not required for the import of PB2 into mitochondria by showing that PB2 associates with mitochondria in MAVS knockout mouse embryo fibroblasts. Instead, we find that amino acid residue 9 in the N-terminal mitochondrial targeting sequence is a determinant of the mitochondrial importof PB2, differentiating the localisation of PB2 of human from that of avian influenza Avirus strains. We also show that a virus encoding non-mitochondrial PB2 is attenuated in MEFs compared with an isogenic virus encoding mitochondrial PB2, in a MAVS-independent manner, suggesting a role for PB2 within the mitochondrial matrix. This work extends our understanding of the interplay between influenza virus and mitochondria.